2015
DOI: 10.1007/978-94-017-9642-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Volvocine Algae: From Simple to Complex Multicellularity

Abstract: The evolution of multicellularity provided new ways for biological systems to increase in complexity. However, although high levels of complexity have indeed been attained in several multicellular lineages, natural selection does not necessarily favor complex biological systems. Why and how, then, has complexity increased in some lineages? We argue that the volvocine green algae (Volvox and its relatives) are a uniquely valuable model system for understanding the evolution of multicellular complexity. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 102 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…Differentiation of somatic cells is regulated by RegA, a protein that suppresses photosynthesis and thereby prevents division (88). Interestingly, phylogenetic studies revealed that a close homolog of RegA is involved in photoacclimation, a plastic response that can be triggered by light deprivation (39,89). In the unicellular ancestor, photoacclimation was likely required for cells to adjust to the diurnal light cycle: inhibiting photosynthesis during light limitation prevents oxidative stress.…”
Section: Conflictmentioning
confidence: 99%
“…Differentiation of somatic cells is regulated by RegA, a protein that suppresses photosynthesis and thereby prevents division (88). Interestingly, phylogenetic studies revealed that a close homolog of RegA is involved in photoacclimation, a plastic response that can be triggered by light deprivation (39,89). In the unicellular ancestor, photoacclimation was likely required for cells to adjust to the diurnal light cycle: inhibiting photosynthesis during light limitation prevents oxidative stress.…”
Section: Conflictmentioning
confidence: 99%
“…Multicellularity comes in many forms and complexity levels, ranging from simple cell aggregations, colonies, films or filaments to the most complex organisms known (Szathmary & Smith, ; Rokas, ; Fairclough, Dayel, & King, ; Knoll, ; Niklas & Newman, ; Richter & King, ; Sebé‐Pedrós et al ., ; Niklas, ; Rainey & de Monte, ; Umen, ; Aguilar, Eichwald, & Eberl, ; Herron & Nedelcu, ). While simple cell aggregations and colonies evolved at least 25 times in both pro‐ and eukaryotes (Grosberg & Strathmann, ; Rokas, ), complex multicellularity has evolved in up to five major groups: animals, embryophytes, red and brown algae (Knoll, ; Claessen et al ., ; Niklas, ; Umen, ; Cock et al ., , ; Nagy, ; Niklas & Newman, ; Sebé‐Pedrós, Degnan & Ruiz‐Trillo, ), and fungi.…”
Section: Introduction: Simple and Complex Multicellularitymentioning
confidence: 99%
“…Simple and complex multicellularity are distinguished based on the proportion of cells in direct contact with the environment (i.e. all versus some), the extent of cellular differentiation, cell adhesion, communication, a developmental program and programmed cell death (PCD) (Cock et al ., ; Knoll, ; Knoll & Hewitt, ; Herron & Nedelcu, ). Complex multicellularity is usually used with reference to three‐dimensional differentiated structures, although how (and whether) it is defined varies widely across studies.…”
Section: Introduction: Simple and Complex Multicellularitymentioning
confidence: 99%
See 1 more Smart Citation
“…Simple multicellular organisms exhibit phenotypes based on multiple, attached cells, arising either through the aggregation of numerous unicellular individuals, or through the lack of total separation following the division of a single‐celled progenitor (Grice & Degnan, ; Herron & Nedelcu, ). The simplest multicellular phenotypes (i.e., organisms exhibiting simple multicellularity) include sheets, clusters, and chains of physically attached cells that largely remain in direct contact with the external environment and exhibit limited intercellular differentiation, communication, and resource exchange (Knoll & Hewitt, ).…”
Section: Introduction —Animals Are Trophically Uniquementioning
confidence: 99%